High-Frequency Detection of fosA3 and blaCTX–M–55 Genes in Escherichia coli From Longitudinal Monitoring in Broiler Chicken Farms - Menck-Costa, Maísa Fabiana; Baptista, Ana Angelita Sampaio; Gazal, Luiz Eduardo de Souza; Justino, Larissa; Sanches, Matheus Silva; de Souza, Marielen; Nishio, Erick Kenji; Queiroz dos Santos, Beatriz; Cruz, Victor Dellevedove; Berbert, João Vitor Monteiro; Gonçalves, Bruna Carolina; Andrade, Galdino; et al. (Frontiers in Microbiology, 2022)
Considering the worrying emergence of multidrug resistance, including in animal husbandry and especially in food-producing animals, the need to detect antimicrobial resistance strains in poultry environments is relevant, mainly considering a One Health approach. Thus, this study aimed to conduct longitudinal monitoring of antimicrobial resistance in broiler chicken farms, with an emphasis on evaluating the frequency of resistance to fosfomycin and β-lactams. Escherichia coli was isolated from broiler chicken farms (cloacal swabs, meconium, poultry feed, water, poultry litter, and A. diaperinus) in northern Paraná from 2019 to 2020 during three periods: the first period (1st days of life), the second period (20th to 25th days of life) and third period (40th to 42nd days of life). Antibiogram tests and the detection of phenotypic extended-spectrum β-lactamase (ESBL) were performed, and they were confirmed by seaching for genes from the blaCTX-M group. The other resistance genes searched were mcr-1 and fosA3. Some ESBL blaCTX-M-1 group strains were selected for ESBL identification by sequencing and ERIC-PCR analysis. To determine the transferability of the blaCTX-M-1- and fosA3-carrying plasmids, strains were subjected to conjugation experiments. A total of 507 E. coli were analyzed: 360 from cloacal swabs, 24 from meconium samples, 3 from poultry feed samples, 18 from water samples, 69 from poultry litter samples, and 33 from A. diaperinus samples. Among the strain isolate, 80% (406/507) were multidrug-resistant, and 51% (260/507) were ESBL-positive, with the blaCTX-M-1 group being the most frequent. For the fosA3 gene, 68% (344/507) of the strains isolated were positive, deserves to be highlighted E. coli isolated from day-old chickens (OR 6.34, CI 2.34-17.17), when compared with strains isolated from other origins (poultry litter, A. diaperinus, water and poultry feed). This work alerts us to the high frequency of the fosA3 gene correlated with the CTX-M-1 group (OR 3.57, CI 95% 2.7–4.72, p < 0.05), especially the blaCTX-M-55 gene, in broiler chickens. This profile was observed mainly in day-old chicken, with a high percentage of E. coli that are multidrug-resistant. The findings emphasize the importance of conducting longitudinal monitoring to detect the primary risk points during poultry production.